(untitled) (Global Journal of Human-Social Science, 2016)
This paper is about the impact of World War I 1914- 1918 on the cocoa industry in Ghana Scholars have examined the impact of the Great War on African political and economic sectors but have downplayed the War s impact on African economies most especially cocoa industry in West Africa I examine the effects of the war-time trade restrictions on cocoa industry in Ghana which by then was the world s largest producer of cocoa in order to show the impact of the international political economy on dependent economies as well as the consequences of economic dependence on external market Although the quantity of cocoa exported from Ghana increased from 1915 there was no corresponding increase in value due to the restriction of trade and suspension of market as the logic of the economy The result of this was the abandonment of cocoa farms and economic downturn of cocoa farmers